Space shuttle legacy how we did it and what we learned - Launius, Roger D.; Krige, John; Craig, James I.; Allen, Ned (Library of flight series, 2013)
This book, more than any other, distills and captures the historical essence of the Space Shuttle program from its post-Apollo inception to its winding down and retirement in 2011. The Shuttle program is the single most significant, and among the most inspirational, science and technology programs in human history to date.